Strategi Branding dan Pembentukan Kesadaran Merek melalui Konten Visual Media Sosial Instagram - Ari Ramadzan; Dody Iskandar (Bandung Conference Series: Public Relations, 2024)
Abstract. Nowadays, the easily accessible nature of the internet is able to reach unlimited audiences. That is why business actors such as coffee shops are starting to use social media to spread information and create awareness of their products or services. One of them is a coffee shop in Bandung City, Cap Dangu. Utilizing visual media content on features on Instagram creates very good impressions and enthusiasm from coffee business people or coffee connoisseurs. Especially at the "Tour De Loa" event, an event showing product casings and visuals about Loa Coffee beans. The aim of this research is to find out and analyze branding strategies and the formation of brand awareness through visual media content at the "Tour De Loa" event on Instagram Coffe Shop Cap Dangu social media. This event was chosen because it was exclusive or was being held for the first time by several coffee activist initiators to be held at Cap Dangu. This event is an urgency for the development of the superiority of West Javanese coffee beans. This research uses a qualitative approach with case studies as the method. Data collection techniques were obtained by interviews, observation and documentation relevant to the research. The research subjects were key informants who were directly involved in the "Tour De Loa" event and Instagram visual media content manager Cap Dangu. The results of the research found that the marketing communication strategy for branding and forming brand awareness through visual content on Cap Dangu's Instagram social media through the Tour De Loa event is through a promotional mix that emphasizes events and experiences gained by consumers as well as public relations and publicity. (Public Relations and Publicity). The visual content focuses on the branding that you want to promote, namely coffee and design. This pattern is visualized in the form of education post and event post content which is aligned with a unified design. Cap Dangu also strengthens its branding with a combination of the color identities of Cap Dangu and Tour De Loa by making the key visual color in the visual content. Abstrak. Dewasa ini, sifat internet yang mudah di akses dapat menjangkau khalayak tanpa batas. Itu sebanya para pelaku usaha seperti kedai kopi mulai memanfaatkan media sosial untuk menyebarkan informasi dan membentuk kesadaran produk atau jasanya. Salah satunya ialah kedai kopi di Kota Bandung, Cap Dangu. Memanfaatkan konten media visual pada fitur di Instagram memunculkan impresi sangat baik dan antusiasme dari para pebisnis kopi atau pun penikmat kopi. Terutama pada event “Tour De Loa”, event show casing produk dan visual mengenai biji Kopi Loa. Tujuan dari penelitian ini, untuk mengetahui dan menganalisis strategi branding dan pembentukan kesadaran merek melalui konten media visual pada event “Tour De Loa” dimedia sosial Instagram Coffe Shop Cap Dangu. Event ini dipilih karena eksklusif atau baru pertama kali dicanangkan oleh beberapa inisiator pegiat kopi yang diselenggarakan di Cap Dangu. Event ini menjadi urgensi untuk perkembangan keunggulan biji kopi khas Jawa Barat. Penelitian ini menggunakan pendekatan kualitatif dengan studi kasus sebagai metode. Teknik pengumpulan data didapat dengan wawancara, observasi dan dokumentasi yang relevan dengan penelitian. Subjek penelitian merupakan key informant yang terlibat langsung dalam acara “Tour De Loa” dan pengelola konten media visual Instagram Cap Dangu. Hasil penelitian ditemukan strategi komunikasi pemasaran untuk branding dan membentuk kesadaran merek melalui konten visual media sosial Instagram Cap Dangu lewat event Tour De Loa adalah dengan melalui bauran promosi yang menonjolkan pada acara dan pengalaman (Events and experiences) yang didapat oleh konsumen serta hubungan masyarakat dan publisitas (Public Relation and Publicity). Adapun konten visual dititik beratkan pada branding yang ingin diusung yaitu coffee and design. Pattern tersebut divisualisasikan dalam bentuk konten education post dan event post yang diselaraskan dengan kesatuan desain. Cap Dangu juga memperkuat branding pada dengan perpaduan identitas warna Cap Dangu dan Tour De Loa dengan menjadikan warna key visual pada konten visual.